Analisis Overall Equipment Effectiveness (OEE) dan Six Big Losses Pada Sistem Coal Handling Sebagai Upaya Meningkatkan Kinerja Produksi PT XYZ - Erlangga Dzaky Atha'ulah (Fakultas Rekayasa dan Teknologi Industri, 2026)
PT XYZ is a coal-fired Steam Power Plant (PLTU) with a capacity of 2×15 MW located in the Kariangau Industrial Zone, Balikpapan, East Kalimantan. The coal handling system at this facility faces several operational issues, including coal spillage along conveyor belts and transfer chute points, crushed coal particle sizes that do not meet specifications, and blockages in the coal feeder that collectively reduce overall production effectiveness. This study aims to measure the effectiveness of the coal handling system using the Overall Equipment Effectiveness (OEE) method, identify the dominant sources of operational losses through Six Big Losses analysis, and formulate targeted improvement recommendations. Data were collected qualitatively through interviews and Likert-scale questionnaires administered to 8 coal handling operators and technicians, then processed using the Min-Max Optimization method to convert questionnaire scores into OEE component percentages. The analysis results show an Availability Rate of 91%, a Performance Rate of 88%, and a Quality Rate of 64%, yielding an overall OEE value of 51%, which remains below the JIPM world-class standard of 85%. Based on the Six Big Losses analysis, Process Defect losses emerged as the most dominant loss factor at 72%, attributed to coal spillage and non-conforming crush sizes. The proposed improvement recommendations include the installation of a double sealing skirt rubber system, implementation of a Zero Spillage Initiative program, adoption of Defect Mapping Area, and control of the coal feed rate to the Crusher through adjustment of Vibratory Feeder speed.